The Application of Origami Therapy in The Elderly with Impaired Cognitive Function: A Case Study - Salsabila, Nada; Witdiawati, Witdiawati; Sari, Sheizi Prista (Journal of Nursing Care, 2025)
Older adults are prone to cognitive decline, which impacts their quality of life. While origami therapy is known to improve concentration and fine motor skills, studies on its effect on cognitive function in older adults remain limited. As a non-pharmacological intervention, origami folding offers cognitive stimulation through enjoyable activities. Objective to determine the effectiveness of origami therapy in improving cognitive function in an older adult with cognitive impairment. This study employed a case study design involving a 71-year-old resident of Griya Lansia Garut. The intervention was carried out in six sessions over a period of ten days. Cognitive function was assessed using a standardized cognitive assessment tool on the first and last day of the intervention. The client’s score increased from 18 to 22, which remains within the mild cognitive impairment category but indicates improvement. Enhancements were observed in the client’s ability to follow instructions, recall folding steps, name objects, and orient to time. These findings suggest that origami folding may help enhance cognitive funtion in older adults, particularly in attention, memory, and orientation. Further research with a larger sample size is recommended to explore the broader effectiveness of this intervention.